An Analysis of Financial Performance and Regional Capability Mapping in Regencies and Cities of Nusa Tenggara Barat Province (2018-2022) - Sadaruddin, Sadaruddin; Abdul Manan; Siti Sriningsih; Driss Tsouli; Samuel Asuamah Yeboah; Bazira Bigawa Abel; Mohammed Ahmar Uddin; Farid Ahmad; Falah Abdul Redha Al Kharassani (Economy and Finance Enthusiastic, 2024)
The successful implementation of regional autonomy is closely linked to financial performance, which serves as a key indicator in assessing the effectiveness of regional autonomy. The relatively low Local Original Revenue (PAD) in the regencies and cities of Nusa Tenggara Barat Province is attributed to limited capacity in exploring income sources compared to their potential. This study employs a descriptive quantitative approach, using secondary data sourced from the Ministry of Finance’s official portal for the years 2018-2022. The data analysis techniques used include Financial Performance Analysis, Financial Capability Index (IKK) Analysis, and the Quadrant method for mapping regional financial capability. The findings reveal that the average Independence Ratio of regencies and cities during the five-year period remains in the instructive (very low) category, with only Mataram City demonstrating a consultative (low) relationship pattern. Mataram City also exhibited the highest degree of fiscal decentralization, at 26.74%. The PAD Effectiveness Ratio is categorized as highly effective for Lombok Barat Regency, Dompu Regency, Sumbawa Barat Regency, Mataram City, and Bima City. However, regional financial performance in most districts/cities of Nusa Tenggara Barat Province from 2018 to 2022 is relatively inefficient. Six districts/cities, including Lombok Timur Regency, Mataram City, and Bima City, are categorized as having high financial capability, with an IKK above 43%. According to the Quadrant method, three districts/cities—Lombok Timur Regency, Lombok Barat Regency, and Mataram City—are positioned in Quadrant I, with a Share value greater than 12.1% and a Growth value greater than -0.6%.